Gastrointestinal Stromal Tumors: A Rare Neoplasm Presenting with Gastrointestinal Bleeding - Fardah Akil; HAM Akil; Tajuddin Tjambolang; N K Sungowati; M Adnan; Bachtiar Murtala; Junus Alkatiri; Santa Jota (The Indonesian Society for Digestive Endoscopy, 2007)
Gastrointestinal stromal tumors (GIST) are rare tumors of the gastrointestinal (GI) tract that arise from primitive mesenchymal cells. GISTs occur throughout the GI tract but are usually located in the stomach and small intestine. GISTs are known with myoid, neural or mixed features of differentiation. Clinical findings are gastrointestinal bleeding, abdominal pain, and weight loss. GISTs express a heterogeneous clinical course not easily predicted. The histologic features that correlate best with development of recurrence and metastasis are mitotic activity, tumor size and the presence of tumor necrosis and most recently, mutation in the c-kit gene. Some authors specifically use the term GIST to refer to only those mesenchymal tumors that express CD117, whereas others believe that the diagnosis can be made in the absence of CD117 positivity based on clinical and morphologic features. Surgical resection remains the treatment of choice, since chemotherapy and radiation are ineffective. Long-term follow-up is imperative and recurrence rates are high. We report the case of a 60 years old female patient who presented with intermittent melena, chronic dyspepsia, and anemia. Upper digestive tract endoscopy showed a submucosal tumor, broad-based, centrally ulcerated, projection of 5 cm in the gastric corpus-antral wall as the cause of the upper gastrointestinal bleeding. Endoscopic biopsies were negative for neoplastic changes. After triple eradication therapy of Helicobacter pylori and treatment continued with proton pump inhibitor agent, the patient underwent distal gastrectomy with Billroth-I reconstruction. Histopatological studies on the surgical resection specimen revealed a GIST of smooth muscle with spindle cell, no evidence of mitotic activity but of uncertain biological behavior. One year after surgery the patient is was improved with no signs of residual malignancy. However, metastases were found later in the liver in the next two year. Keywords: GIST, stromal tumor, surgery, C-kit